HUBUNGAN ANTARA PEMETAAN LINEAR DAN BILINEAR - Ruhama, Mustafa A. H. (Delta-Pi: Jurnal Matematika dan Pendidikan Matematika, 2013)
Let U, V and W are vector spaces at the same field, phi : U ? V is linear mapping and   is complex numbers.   L (U,V) the collection of all linear mapping  phi : U ? V . If V = C that  is linear  functional. Let phi : U ? V   bilinear mapping, if  W = C that phi  is bilinear functional. The collection of all bilinear mapping phi : U x V ? W denoted with B(U,V,W). Based on the explanation above, problems we will discuss about relation  between linear mapping, bilinear mapping and bilinear functional, some properties at bilinear mapping.